Professional Office Business Application Development: Using Microsoft Office SharePoint Server 2007 and VSTO - Pox Steve (Wiley, 2008)
Office business application (OBA) development leverages the Office environment with SharePoint Server 2007 and Visual Studio® tools for Office (VSTO) to build solutions that integrate the most important details of design, deployment, and development to Office tools that are used every day. Understanding the key elements of building and deploying an OBA is integral to bridge the gap between business data and the people who need it.